Integration of HOTS-Based Questions on the Theme â€œThe Beauty of Togethernessâ€ Through Fun Thinkers Learning Media for Grade IV Elementary School Students - Pranyani, Ni Komang Ayu Indah; Agustiana, I Gusti Ayu Tri; Simamora, Alexander Hamonangan (International Journal of Elementary Education, 2021)
The lack of use of learning media used for delivering material makes it difficult for students to understand the material. This study aims to develop media for fun thinkers based on HOTS questions for fourth grade elementary school students on theme 1, the beauty of togetherness. The development is carried out based on the ADDIE model procedure. The subjects in this development research are media fun thinkers based on HOTS questions for elementary school students grade IV theme 1 the beauty of togetherness while the object in this study is the validity of the media fun thinkers developed. This development research method is a qualitative and quantitative statistical analysis method. The data collection used is a questionnaire method with data collection instruments in the form of a rating scale by giving assessment instruments to 2 subject matter experts, 2 media experts, 2 practitioner responses, and 10 students as responses. The data obtained was calculated using the mean formula to determine the average media validity score. The average validity score of media fun thinkers based on HOTS questions in terms of material/assessment experts is 4.79 with very valid criteria, in terms of media experts it is 4.43 with very valid criteria, in terms of practitioner responses it is 4.63 with very valid criteria, and in terms of response students of 4.95 with very valid criteria. Based on the analysis conducted, the media for fun thinkers based on HOTS questions for elementary school students in grade IV, theme 1, the beauty of togetherness developed is valid and suitable for use in the learning process.